MP56: A National survey of burnout and mentorship programs amongst Royal College Emergency Medicine residents. (May 2019) - Liu, R.; van Aarsen, K.; Sedran, R.; Lim, R.
Abstract : Introduction : In recent years, there has been growing interest in the field of physician wellness and burnout. Past research has shown that the prevalence of burnout is non-uniform between specialties and is most prevalent amongst emergency medicine physicians. Additionally, burnout can be observed amongst individuals early in their medical careers, including medical students and residents. To date, there is no national perspective of burnout amongst Canadian Royal College of Emergency Medicine (EM) residents. Our study looks to provide a national survey of burnout in this population as well as characterize mentorship programs at training sites.Methods : An anonymous electronic survey was e-mailed to Canadian EM residents via local program directors. Characteristics of mentor-mentee relationships and quality of residents' mentorship experiences were assessed on a 6-point Likert scale. The Maslach Burnout Inventory – Human Services Survey (MBI-HSS) for medical personnel was used to assess burnout on three dimensions (emotional exhaustion, depersonalization and personal accomplishment). Burnout was dichotomized as present or absent if the MBI criteria are met (emotional exhaustion score > 26 or depersonalization score > 9 or personal accomplishment <34).Results : To date, 52 responses have been collected. Respondents are primarily male (63%) and in their PGY year 1-3 (71%). Responses were collected from 6/14 (43%) of eligible programs. 84% of residents currently had an emergency medicine mentor. Of these, 8% were dissatisfied with their residency's mentorship program and 55% were satisfied/very satisfied. 72% of residents met the threshold for burnout in at least one dimension of the MBI (3 dimensions = 17%; 2 dimensions = 17%; 1 dimension = 38%) and 13% cited considering suicide during their training.Conclusion : Results thus far suggest significant burnout amongst Royal College of Emergency Medicine residents. Alarmingly, 13% of responders cited having contemplated suicide during their training. These results point to an important opportunity to better support EM residents during their training to improve wellness and reduce burnout. Our findings suggest a high prevalence of residents with established mentors and future analyses will examine the correlation between mentorship characteristics and resident burnout levels.